Literasi Sadari pada Perempuan Kota di Masyarakat Marginal - Irma, Irma; Kusbandiyah, Jiarti; Wahyuni, Ayu Sri; Mulyani, Sri; Aprilina, Aprilina (Poltekkes Kemenkes Padang, 2023)
Literacy in self-breast examination (SADARI) still lacks attention from the community. Urban women in marginal communities even have limited access to health information. As a result, early detection of breast cancer remains a significant challenge for them. This study aims to obtain an overview of SADARI literacy among urban women in marginal communities. The study was conducted using a descriptive quantitative approach with a random sampling technique. The respondents were 79 women from the Az Zahra fisherman community in Ujung Tanah District, Makassar. Data collection was carried out using a questionnaire sheet and observations consisting of 20 questions. The collected data were analyzed with descriptive statistics using Excel. The early cancer detection variables used are self-breast examination (SADARI) and clinical breast examination (SADANIS). The results of this study indicate that SADARI literacy among urban women in marginal communities is still low. There are five indicators measured in this study, with the results showing respondents who have a good understanding of the purpose of SADARI (27%), the benefits of SADARI (11%), how to perform SADARI (7%), the appropriate time to perform SADARI (13%), and the signs found and the appropriate time to perform SADANIS (23%). This research can be a reference for the government to promote the socialization of early breast cancer detection that reaches marginal communities.